1979
DOI: 10.1177/27.1.374627
|View full text |Cite
|
Sign up to set email alerts
|

Preselection of alarms in a hybrid system for screening of cervical cancer.

Abstract: In this report, a preselection of alarms in a system for automated screening of cervical cancer based on depositing the cell sample linearly as a "cell trace" on a tape and analyzing it at different decision levels with increasing complexity, and preliminary results on analyzing cervical material with this system are discussed. The "cell trace" is analyzed with the slit-scan technique. Six parameters are computed: 1) cellular diameter; 2) nuclear diameter; 3) nuclear fluorescence (acriflavin-Feulgen) as nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Introduction of the slit-scan technique has also indicated that the false alarms are the main obstacle in the development of an automated prescreening instrument (150,214). Using the slit-scan technique six different paramet,ers could be evaluated (208,215) and the method looks promising.…”
Section: Female Genital Tractmentioning
confidence: 99%
“…Introduction of the slit-scan technique has also indicated that the false alarms are the main obstacle in the development of an automated prescreening instrument (150,214). Using the slit-scan technique six different paramet,ers could be evaluated (208,215) and the method looks promising.…”
Section: Female Genital Tractmentioning
confidence: 99%